2022
DOI: 10.3390/cells11203305
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal Plasma Gelsolin Is an Immunosuppressive Mediator in the Ovarian Tumor Microenvironment and a Determinant of Chemoresistance

Abstract: Ovarian Cancer (OVCA) is the most fatal gynecologic cancer and has a 5-year survival rate less than 45%. This is mainly due to late diagnosis and drug resistance. Overexpression of plasma gelsolin (pGSN) is key contributing factor to OVCA chemoresistance and immunosuppression. Gelsolin (GSN) is a multifunctional protein that regulates the activity of actin filaments by cleavage, capping, and nucleation. Generally, it plays an important role in cytoskeletal remodeling. GSN has three isoforms: cytosolic GSN, pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 115 publications
0
3
1
Order By: Relevance
“…Interestingly, another recent study contradicts our findings and the findings of Arentz et al (2023), demonstrating that the expression and secretion of GSN were higher in chemo-resistant OC cells than in chemo-sensitive OC cells [80]. The supporting study by Onuma et al (2022) [81] suggested that higher levels of GSN prevent cisplatin from dissociating GSN from the FLIP-ITCH complex, thus preventing caspase-3 and -8 activation and caspase-mediated GSN cleavage and thereby inhibiting apoptosis in chemo-resistant OC cells. However, further analysis is needed to understand the role of GSN in OC.…”
Section: Pathogenic Role Of Genes Identified In Platinum-paclitaxel S...contrasting
confidence: 85%
“…Interestingly, another recent study contradicts our findings and the findings of Arentz et al (2023), demonstrating that the expression and secretion of GSN were higher in chemo-resistant OC cells than in chemo-sensitive OC cells [80]. The supporting study by Onuma et al (2022) [81] suggested that higher levels of GSN prevent cisplatin from dissociating GSN from the FLIP-ITCH complex, thus preventing caspase-3 and -8 activation and caspase-mediated GSN cleavage and thereby inhibiting apoptosis in chemo-resistant OC cells. However, further analysis is needed to understand the role of GSN in OC.…”
Section: Pathogenic Role Of Genes Identified In Platinum-paclitaxel S...contrasting
confidence: 85%
“…An escalating number of studies underscore the tumor‐related ECM as a significant impediment to achieving enhanced success in cancer immunotherapy cases 31,32 . Multiple investigations have delineated that the tumor‐related extracellular matrix (ECM) actively propels the processes of tumor cell growth, invasion, metastasis, and angiogenesis, while simultaneously thwarting programmed cell death and impeding drug diffusion 33,34 . Consequently, gaining an in‐depth understanding of the intricate interplay between ECM and the tumor immune response is essential for realizing the potential of targeting the tumor‐associated ECM to enhance the efficacy of cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The role of these proteins in cancer has remained unclear due to conflicting results: while some studies have classified them as oncogenes, others have proposed that they predominantly encompass tumor suppressor functions [ 89 , 90 ]. In addition, only a limited number of studies have investigated the potential role of these proteins in the development of resistance in cancer, particularly in ovarian cancer and gliomas [ 91 , 92 ]. Therefore, it would be necessary to investigate the potential role of all these under-expressed proteins and their various complexes in the development of resistance to anti-HER2 therapies.…”
Section: Discussionmentioning
confidence: 99%